1990
DOI: 10.1002/joc.3370100304
|View full text |Cite
|
Sign up to set email alerts
|

A quasi‐biennial oscillation in the intensity of the intra‐seasonal oscillation

Abstract: The interannual and annual variations in the intra-seasonal oscillation (ISO) are examined using upper air radiosonde data at Singapore. Spectral analysis of the zonal wind using the maximum entropy method (MEM) was made for each season, starting from the autumn of 1960 through to 1985. It is shown that the strongest signal of the I S 0 occurs during the Northern Hemisphere winter, while the weakest occurs in the Northern Hemisphere summer.The main finding of this study is a quasi-biennial oscillation (QBO) in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

1990
1990
2025
2025

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 11 publications
1
7
0
Order By: Relevance
“…The impact of stratospheric circulation on the MJO has been reported in connection to the QBO (Kuma, 1990;Yoo and Son, 2016). The present results suggest that the change in TTL stability due to anomalous stratospheric downwelling had an impact on the sudden termination of the MJO event in early December 2011 (Fig.…”
Section: Discussion and Concluding Remarkssupporting
confidence: 72%
“…The impact of stratospheric circulation on the MJO has been reported in connection to the QBO (Kuma, 1990;Yoo and Son, 2016). The present results suggest that the change in TTL stability due to anomalous stratospheric downwelling had an impact on the sudden termination of the MJO event in early December 2011 (Fig.…”
Section: Discussion and Concluding Remarkssupporting
confidence: 72%
“…Concurrently, Tan (1980, 1982) suggested a similar association between these polar stratospheric warmings and the QBO (see also Wallace and Chang, 1982). The conclusions of recent studies by Kuma (1990), Yasunari (1989), Enfield (1990), , Knaff (1991), Knaff et al, (1992), Gray et al, ( , 1992 and Angell (1992) argue for direct linkage between the stratospheric QBO and various tropospheric and oceanic data series. Van loon and Labitzke (1988), , and Sheaffer (1991) have also presented evidence of active modulation of ENSO-linked teleconnections into mid-latitude areas by the stratospheric QBO.…”
Section: Related Researchmentioning
confidence: 87%
“…The 30-60 day oscillation Kuma (1990) using Singapore (1.4*N latitude) rawinsonde data, observed a QBO-linked variation in the intensity of the 30-60 day oscillation (ISO). This effect was noted to be especially pronounced during the Austral summer (December to March) period.…”
Section: Regional Anomalies In Surface Datamentioning
confidence: 99%
“…A relationship between the QBO and the MJO was first noted by Kuma (1990), who found that the intensity of upper-tropospheric winds associated with the MJO was well correlated with the QBO. Little subsequent work was done until more recent studies, beginning with Yoo and Son (2016), spurred renewed interest in the topic (Yoo and Son 2016;Marshall et al 2017;Son et al 2017;Hood 2017;Nishimoto and Yoden 2017;Lee and Klingaman 2018;Zhang and Zhang 2018;Hendon and Abhik 2018;Wang et al 2018).…”
Section: Introductionmentioning
confidence: 84%